PENGARUH KAMPANYE DIGITAL “EXPLORE BALI” TERHADAP PENINGKATAN KUNJUNGAN WISATAWAN DOMESTIK KE DENPASAR - I Wayan Muliana (Nusantara Hasana Journal, 2024)
This study aims to analyze the impact of the "Explore Bali" digital campaign on the increase in domestic tourist visits to Denpasar. By adopting a quantitative approach and an explanatory design, the research involves 384 respondents, who are domestic tourists visiting Denpasar and exposed to the digital campaign. Data collection was conducted through online surveys, secondary data analysis, and web analytics. The results of the simple linear regression analysis show that the "Explore Bali" digital campaign has a positive and significant effect on the increase in domestic tourist visits, with a coefficient of determination (R²) of 0.462. Descriptive analysis reveals that respondents have a very positive perception of the digital campaign, with content appeal being the highest indicator. Intention to revisit becomes the highest indicator in the variable of increasing tourist visits. These findings support the Diffusion of Innovations theory and the AIDA Model in the context of digital tourism marketing.